2022
DOI: 10.3389/feart.2022.910666
|View full text |Cite
|
Sign up to set email alerts
|

Links of Hydrogen Sulfide Content With Fluid Components and Physical Properties of Carbonate Gas Reservoirs: A Case Study of the Right Bank of Amu Darya, Turkmenistan

Abstract: Hydrogen sulfide (H2S) in carbonate gas reservoirs shows strong relevance with the natural gas components and has an obvious impact on reservoir types and their petrophysical properties. In this work, core and fluid samples were collected from the Right Bank of Amu Darya reservoirs, Turkmenistan. Then, fluid composition analysis and flash evaporation experiments were performed to investigate the components of reservoir fluid. Petrophysical properties, that is, porosity and permeability, and micropore structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Asaoka et al 20 revealed the temporal and spatial distribution of sulfur forms in marine sediments in Osaka Bay, Japan, through the combined method of lead sulfide ribbon detection tube and X-ray absorption fine structure spectroscopy. Cheng et al 21 showed that TSR was the main reason for the high H 2 S content in carbonate reservoirs through the analysis of the physical properties and thermodynamic conditions of carbonate reservoirs. In order to determine the geothermal history of the coal seams, Dongna and Meiling 22 calculated the thermal evolution temperature per capita using vitrinite reflectance, providing strong evidence for the genetic analysis of H 2 S gas in coal seams.…”
Section: Introductionmentioning
confidence: 99%
“…Asaoka et al 20 revealed the temporal and spatial distribution of sulfur forms in marine sediments in Osaka Bay, Japan, through the combined method of lead sulfide ribbon detection tube and X-ray absorption fine structure spectroscopy. Cheng et al 21 showed that TSR was the main reason for the high H 2 S content in carbonate reservoirs through the analysis of the physical properties and thermodynamic conditions of carbonate reservoirs. In order to determine the geothermal history of the coal seams, Dongna and Meiling 22 calculated the thermal evolution temperature per capita using vitrinite reflectance, providing strong evidence for the genetic analysis of H 2 S gas in coal seams.…”
Section: Introductionmentioning
confidence: 99%
“…thermochemical sul phate re duc tion -TSR, mi cro bial sul phate re duc tion -MSR, ther mal de com po si tion of sul phur-con tain ing or ganic compounds of oil and or ganic mat ter, re ac tion of el e men tal sul phur with hy dro car bons, vol ca nic and plutonic pro cesses (Orr, 1977;Krouse et al, 1988;Machel et al, 1995;Worden et al, 1995;Worden and Smalley, 1996;Machel, 2001;Zhu et al, 2005;Zhang et al, 2008). This gas is com monly found as so ci ated with sul phate and car bon ate rock units form ing sour nat u ral gas res er voirs (Worden and Smalley, 1996;Aali and Rahmani, 2012;Liu et al, 2014;Bilkiewicz and Kowalski, 2020;Kotarba et al, 2020;Torghabeh et al, 2021;Cheng et al, 2022). Be sides its oc currence in these nat u ral gas res er voirs, the or i gin, mi gra tion and ac cu mu la tion of H 2 S has been also stud ied in con nec tion with coal seams (Liu et al, 2012;Deng et al, 2014;Tan et al, 2020;Xie et al, 2021), pe tro leum fields (Kotarba et al, 2017b) and the ex plo ra tion, de sign and op er a tion of geo ther mal fa cil i ties (D'Amo re et al, 1990;Mayrhofer et al, 2014;Jácome Paz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%